The Analysis of Students’ Exchange Program of Independent Learning in Indonesia: MBKM-PMM - Yasa, Shalsa Midina Malidha; Ulfaika, Romlah; Arifin, Arifin (Universitas Borneo Tarakan, 2024)
This research’s purpose is to analyze the experience of students in Indonesia that participated on Indonesia Student’s Exchange Program that was held by the government. The research resulted the specific experience whether it is a good one or a bad one related to the program with advise from the students. The data from students is received via Google Form that was shared through social media i.e., WhatsApp Groups. The results show 1. The percentage of the chosen options, 2. The reasons behind the options.. The results of this research can be used as the guidance of improvement for the next system of Student’s Exchange Program.